Primary intraosseous carcinoma arising from odontogenic keratocyst with parotid lymph node metastasis. A case report - Siddesh Shenoy; Rachna Acharya; Ajit D Dinkar (Wolters Kluwer Medknow Publications, 2007)
Squamous cell carcinoma (SCC) arising from odontogenic cyst lining is rare. The exact incidence of carcinoma arising in odontogenic cyst is unknown, but it is estimated to vary between 1 and 2/1000. The pathogenesis is unknown, but a long-standing inflammation and continuous intracystic pressure have been suggested as possible causative factors. Metastasis from these lesions is not common (< 20%), and most of the carcinomas are moderately to well differentiated. To qualify as a primary intraosseous carcinoma, there must be no initial connection with the oral mucosa, overlying skin, or antral or nasal mucosa. This paper presents a case of primary intraosseous carcinoma arising from odontogenic keratocyst in the anterior mandible with metastasis to left parotid lymph nodes.